The Influence of Communication and Competence on the Commitment Which Has Impacts on the Organizational Citizenship Behavior - Ferryal Abadi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
The aim of this research is to analyze and study the influence of communication and competence on commitment which has impacts on organizational citizenship behavior (OCB). The population and sample of this research are the employees in the staff level of garment companies numbering 100 in the Nusantara Bonded Area. Data gathering uses questionnaires, interviews, observation, and documentation. Path analysis is used in processing SPSS software. This study indicate that (1) communication has a significant effect on commitment, while competence is not shown to be significant; (2) OCB can be explained by communication and competence, while commitment is not proven to significantly affect OCB.